Hubungan Anemia Defisiensi Besi dengan Pneumonia pada Anak Usia 6 Bulan – 5 Tahun - Saputra, Novel Widya; Kusumawardani, Tri; Muryawan, Muhammad Heru (Medica Hospitalia : Journal of Clinical Medicine, 2022)
Background Iron deficiency anemia is a health problem in developing countries that causes an increase in the incidence of infection. One of the consequences of infection is pneumonia which is the cause of high morbidity and mortality in children under five around the world. Purpose To determine the relationship between iron deficiency anemia and the incidence of pneumonia infection in children 6 months – 5 years. Methods The study was conducted with a cross sectional design, 27 subjects aged 6 months – 5 years at Bendan Hospital Pekalongan. The characteristics of the subjects studied were age, gender, nutritional status, breast milk, ferritin, hemoglobin and pneumonia. The data obtained were analyzed by contingency test C and logistic regression with a significance level was set at p<0.05.Result Iron deficiency anemia is associated with the incidence of pneumonia, p value < 0.001, with a weak correlation value (0.437). From the results of logistic regression (multivariate) analysis, Hb and ferritin levels had no effect on iron deficiency anemia PR 1.281 (95% CI <0.05), p=1,000 and PR 2.364 (95% CI <0.05), p=0.995. Conclusion There is a weak relationship between iron deficiency anemia and the incidence of pneumonia infection in children under five.. Hemoglobin and ferritin levels are not the dominant variables that affect iron deficiency anemia.